What is quality and how is it achieved? Practitioners' views versus quality models. Issue 1 (1st February 2008) - Hudelson, P; Cléopas, A; Kolly, V; Chopard, P; Perneger, T
Abstract : Background: Quality improvement in healthcare organisations requires structural reorganisation and systems reform, and also the development of an appropriate organisational "culture". Beliefs and attitudes that are thought by experts to be conducive to quality improvement in hospitals include the understanding of healthcare as a complex system, recognition of the importance of coordination of healthcare processes, a positive attitude towards medical error, adherence to the concept of continuous improvement, and a central preoccupation with the patient's welfare. Objectives: To explore the ideas about quality held by hospital-based doctors and nurses in Geneva, Switzerland. Methods: Semi-structured interviews were conducted with 21 doctors and nurses in five hospital departments to explore their ideas about the definition of quality in healthcare, their perceptions about the main barriers to achieving quality healthcare, the factors that facilitate delivery of quality healthcare, and notions of responsibility for ensuring quality healthcare. Results and conclusions: Thematic analysis of the interview data suggested that doctors' and nurses' ideas bear little resemblance to models of quality developed by quality experts. Study participants considered quality of care to be primarily the responsibility of individual practitioners. Quality was seen as mainly dependent on the practitioners' mastery of the technical and interpersonal aspects of care. In contrast, the healthcare system was seen primarily as a source of obstacles to good quality care, providing insufficient resources and imposing an excessive administrative burden. The paper discusses the potential implications of these ideas for the implementation of quality management initiatives.